A magmatic-hydrothermal lacustrine exhalite from the Permian Lucaogou Formation, Santanghu Basin, NW China – The volcanogenic origin of fine-grained clastic sedimentary rocks. (1st May 2018) - Jiao, Xin; Liu, Yiqun; Yang, Wan; Zhou, Dingwu; Li, Hong; Nan, Yun; Jin, Mengqi
Graphical abstract: Highlights: Mantle-derived minerals are rich in lacustrine shale in Permian Lucaogou Formation. Dolomite, diopside and analcime dominate and formed in magmatic-hydrothermal flows. The shale was formed by density granular flows induced by subaqueous eruption. The minerals are tracers of mantle materials and processes in a rift basin. Abstract: Shales in the middle Permian Lucaogou Formation in the intracontinental Santanghu rift basin have been considered as "typical" organic-rich profundal shales for decades. Our study of well cores using petrographic microscope and scanning electron microscopy suggests an otherwise complex hydrovolcanic and hydrothermal origin. This paper describes characteristics of a particular type of the shales, composed of fine-grained detrital minerals and lithic grains. Some of them are orthopyroxene, calcite, peralkaline feldspars, and analcime that are interpreted as derived from peralkaline-alkaline carbonatite, pyroxenite, analcime phonolite, and andesite, whereas others are quartz, dolomite, ankerite, serpentine, and calcite that were precipitated from syndepositional or penecontemporary hydrothermal fluids. Grain size ranges from 0.001 to 2 mm, mostly 0.01–0.1 mm. Well-developed laminae are mostly 0.5–3 mm thick and alternate with tuffaceous dolomicrite. The rocks are interpreted as sublacustrine hydrovolcanic deposits, which had been altered by syndepositional hydrothermal fluids. The interpretation is substantiated by abundant cone-shaped stratigraphic buildups on seismic sections in the basin. This study shows an ancient example of volcanic-hydrothermal deposits in a rift basin.